Agronomic and environmental constraints in North Island dairying and the choice of pasture species - Goold, G.J.; Thomson, N.A.; Duder, F.R. (NZGA: Research and Practice Series, 1985)
Traditionally dairy production in New Zealand has been centred on regions with adequate rainfall and free draining, fertile soils. Within such regions however, considerable variation between properties is observed in the level of dairy production, often attributed to differences in animal management skills. In contrast, the authors of this paper believe that there are important agronomic and environmental constraints to high dairy production and the paper considers, in particular, the role which various pasture species and cultivars can play, in alleviating these constraints.